Anticancer activity of VmCT1 analogs against MCF‐7 cells. (29th November 2017) - Pedron, Cibele Nicolaski; Andrade, Gislaine Patricia; Sato, Roseli Hiromi; Torres, Marcelo Der Torossian; Cerchiaro, Giselle; Ribeiro, Anderson Orzari; Oliveira, Vani Xavier
Abstract : Antimicrobial peptides are considered promising drug candidates due to their broad range of activity. VmCT1 (Phe–Leu–Gly–Ala–Leu–Trp–Asn–Val–Ala–Lys–Ser–Val–Phe–NH2 ) is an α‐helical antimicrobial peptide that was obtained from the Vaejovis mexicanus smithi scorpion venom. Some of its analogs showed to be as antimicrobial as the wild type, and they were designed for understanding the influence of physiochemical parameters on antimicrobial and hemolytic activity. Some cationic antimicrobial peptides exhibit anticancer activity so VmCT1 analogs were tested to verify the anticancer activity of this family of peptides. The analogs were synthesized, purified, characterized, and the conformational studies were performed. The anticancer activity was assessed against MCF‐7 mammary cancer cells. The results indicated that [Glu] 7 ‐VmCT1‐NH2, [Lys] 3 ‐VmCT1‐NH2, and [Lys] 7 ‐VmCT1‐NH2 analogs presented moderated helical tendency (0.23–0.61) and tendency of anticancer activity at 25 μmol/L in 24 hr of experiment; and [Trp] 9 ‐VmCT1‐NH2 analog that presented low helical tendency and moderated anticancer activity at 50 μmol/L. These results demonstrated that single substitutions on VmCT1 led to different physicochemical features and could assist on the understanding of anticancer activity of this peptide family. Abstract : VmCT1 and analogs with antimicrobial activity were tested in order to verify the anticancer activity against MCF‐7 mammary cancer cells of this family of peptides. The results indicated that some analogs presented moderate helical tendency (0.23 to 0.61) and tendency of anticancer activity at 25 μmol/L, and that single substitutions on VmCT1 led to different physiochemical features and could assist on the understanding of the anticancer activity of this peptide family.